Cambridge English. Mindset for IELTS : (Cambridge University Press, 2017)
MINDSET, the multi-level course from the organisation that produces the IELTS test, develops students' English skills and leaves them fully prepared for test day. MINDSET from Cambridge gets you inside the IELTS test with a unique blend of print and online content. Topic-based units organised by skill make it easy to find what you want. Designed for students aiming for Band 7.5 in the Academic Module, this Student's Book Level 3 includes learning strategies, skills practice and exam practice to help you achieve your goal. Online content includes skills modules, Corpus informed language specific modules and Academic Study Skills, plus access to authentic online practice tests in Testbank. *Access code printed on the inside front cover.